Pro- Environmental Behavior and Big Five Personality Traits: Bridging the gap between employees’ behavior and Sustainable Human Resource Policies. - Shanmugam, Vidhya; Maheswari, Sudha (Nepalese Journal of Management Science and Research, 2024)
Pro-environmental behavior, “How individual behavior contributing to environmental sustainability and it is exclusively based on individual volitional choice i.e., it is a cognitive process” and it includes affect (feeling or emotion), motivation (goals or expectations), cognition (thinking), habits and commits. The main purpose of the study is proposing a conceptual model based on sustainable HRM, between – person variability, pro- environmental behavior with effect on environment sustainability further, bridging gap between employees’ behavior to adopt sustainable policies in the organization. The review investigates the activities and attitudes, between – person variability – motivation, intentions and environment sustainability variables. This study gives suggestions to enhance the field of sustainability environment with the aid of PEB and mediating factor as between-in person variability. Further, this study also discuss future research to accept pro-environmental behavior in the organizations.